Dependence of intrinsic rotation reversals on collisionality in MAST. (19th February 2015) - Hillesheim, J.C.; Parra, F.I.; Barnes, M.; Crocker, N.A.; Meyer, H.; Peebles, W.A.; Scannell, R.; Thornton, A.
Abstract: Tokamak plasmas rotate even without external injection of momentum. A Doppler backscattering system installed at MAST has allowed this intrinsic rotation to be studied in ohmic L-mode and H-mode plasmas, including the first observation of intrinsic rotation reversals in a spherical tokamak. Experimental results are compared to a novel 1D model, which captures the collisionality dependence of the radial transport of toroidal angular momentum due to the effect of neoclassical flows on turbulent fluctuations. The model is able to accurately reproduce the change in sign of core toroidal rotation, using experimental density and temperature profiles from shots with rotation reversals as inputs and no free parameters fit to experimental data.